Pickle Juice Intervention for Cirrhotic Cramps Reduction: The PICCLES Randomized Controlled Trial. (13th June 2022) - Tapper, Elliot B.; Salim, Najat; Baki, Jad; Zhao, Zhe; Sundaram, Vinay; Patwardhan, Vilas; Nikirk, Samantha J.
Abstract : INTRODUCTION: Muscle cramps are common among persons with cirrhosis and associated with poor health-related quality of life. Treatment options are limited. We sought to determine whether pickle juice can improve muscle cramp severity. METHODS: We enrolled 82 patients with cirrhosis and a history of >4 muscle cramps in the previous month from December 2020 to December 2021. Patients were randomized 1:1 to sips of pickle juice vs tap water at cramp onset. Our primary outcome assessed at 28 days was the change in cramp severity measured by the visual analog scale for cramps (VAS-cramps, scaled 0–10). Cramps were assessed 10 times over 28 days using interactive text messages. Secondary outcomes included the proportion of days with VAS-cramps <5, change in sleep quality, and global health-related quality of life measured using the EQ-5D. RESULTS: Overall, 74 patients completed the trial, aged 56.6 ± 11.5 years, 54% male, 41% with ascites, 38% with encephalopathy, and model for end-stage liver disease—sodium score 11.2 ± 4.9. Many patients were receiving other cramp therapies at baseline. The baseline VAS for cramps was 4.2 ± 3.4, the EQ-5D was 0.80 ± 0.10, and 43% rated sleep as poor. At trial completion, the respective values for the pickle juice and control arms were −2.25 ± 3.61 points on the VAS for cramps, compared with control tap water (−0.36 ± 2.87), P = 0.03; a proportion of cramp-days with VAS-cramps <5 were 46% vs 35% ( P = 0.2); and the change in sleep quality was not different ( P = 0.1). The end-of-trial EQ-5D was 0.78 ± 0.10 vs 0.80 ± 0.10 ( P = 0.3). No differences in weight change were observed for those with and without ascites. DISCUSSION: In a randomized trial, sips of pickle brine consumed at cramp onset improve cramp severity without adverse events. Abstract :